Pengaruh Modal, Teknologi, Tingkat Pendidikan Dan Jam Kerja Terhadap Pendapatan Umkm Di Kabupaten Sukoharjo - Ade Fitria Sukma Ardini; Arif Nugroho Rachman (Universitas 45 Surabaya, 2024)
This study discusses the effect of capital, technology, education level, and working hours on the income of MSMEs in Sukoharjo Regency. The purpose of this study is to determine the significant influence of capital, technology, education level, working hours on MSME income. Then to find out the capital, technology, education level, and working hours have a simultaneous effect on the income of MSMEs in Sukoharjo Regency. The type of research used is qualitative research. The sample used was 100 respondents and the sampling technique used simple random sampling. Data collection techniques using questionnaires. Then the data were analyzed by classical assumption tests, multiple linear regression analysis, and hypothesis tests using IBM SPSS Statistics 26 software. Based on the results of the analysis, it can be concluded that the variables of capital, technology, education level, and working hours have a positive, significant and simultaneous effect on the income of MSMEs in Sukoharjo Regency.